A multi-protocol architecture for SNMP entities - Lopes, Rui Pedro (2010)
Crescent requirements on the network management area, droved by the successive increase on networks size, internetworking complexity and time-constraint services deployment, impose the omnipresence of technicians and tools. The universality of the interfaces, both for the manager and for the agent sides, is essential to support these requirements. This paper presents a middleware architecture for the development of agents that can be transparently mapped into different management protocol stacks.